Conceptual mapping of shared value creation by the private commercial banks in Bangladesh - Md. Rabiul Islam; Syed Zabid Hossain (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2019)
Creating shared value is the opportunity driven approach of business entities to benefit the less addressed segment of the society through their core products and services. For bank financial institutions, the opportunity driven approach signifies that banking corporations ought to identify bankable needs that are less addressed or unaddressed and invest on purpose to benefit both society and business. The study strives to develop a conceptual model of how Private Commercial Banks (PCBs) in Bangladesh are creating shared value (a popular concept developed by ([Porter ME, Kramer MR], [The big idea: creating shared value; how to reinvent capitalism-and unleash a wave of innovation and growth], [2011])) through reviewing the products and services of PCBs in light of available literature in the field of strategic corporate social responsibility and creating shared value. The model has identified core products and services that are creating shared value for both the bank and the society concurrently. It has also identified factors that are limiting shared value creation capacity of PCBs. Thus, the model will assist the money market policy planners especially bankers to identify the products, services, markets, and value chain that could augment capacity of creating shared value and remove the road-blocks for creating upscale shared value in the developing country context.
Keywords: 650; Creating shared value; Shared value; Strategic banking; Banking on shared value